PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV C SDN 165 PEKANBARU - Linda Gusnita; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT : The problem in this research is a low learning outcomes IPA. The purpose of this research to determine whether the application of guided inquiry learning model can improve learning outcomes IPA grade IV C SDN 165 Pekanbaru.. The research subjects were students of class IV C SDN 165 Pekanbaru totaling 37 students. This research was conducted in two cycles. Each cycle consists of 2 meetings and 1 times daily tests. The data collection instruments in this research is learning outcomes of students, and observation sheet activities of teacher and student. This research was conducted in the form of classroom action research (PTK). In this study, presented an increase in the activities of teachers in the first cycle amounting 79.16% increased in the second cycle of 86.11%, it had increased 6.95%. At the student activity also increased in the first cycle of 73.21%, which then increased in the second cycle amounting 82.14%, with an increase from the first cycle to the second cycle amounting 8.93%. In addition, there is also an increase in learning outcomes of students through repetition end on average student learning outcomes are a base score of 73, an increase in the first daily test became 83.51, from a base score to the first daily test an increase of 10.51 points. In the second daily test an increase of 2.17 points. So that the total average increased to 12.68 points. From these results it can be concluded that the application of guided inquiry learning model can improve student learning outcomes IV C grade SDN 165 Pekanbaru.Keywords : Guided inquiry learning model, Improve learning outcomes IPA